Peran Penjual Perantara terhadap Minat Beli Pembalut Wanita Merek Bagus Nina - Cynthia Leona; Retno Dewanti; Andreas Chang (Binus Business Review, 2014)
Conditions of intense competition and the number of competitors in the napkins industry are quite a lot, so that sanitary napkins manufacturers should be more serious in response to the amount of their market share. Similarly, with Bagus Nina which has a fairly low market share among competitors, this is because the presence of Bagus Nina are fairly new in the toiletries industry. To increase market share and sales, Bagus Nina must find out the purchase intention of their consumer, it is inseparable from the role of intermediaries or channel in distributing products to consumers. Based on that, it was urgently conducted a research about the influence of channel performance towards purchase intention with mediation by brand awareness and brand image with Bagus Nina user in Jabodetabek as the respondents. The purpose of the study is to determine the best path in the form of consumer purchase intention. This research is a descriptive study based on user survey. The method used in this study is path analysis approach with SPSS statistical software. The results of this research indicate that the channel has the effect, directly and indirectly to consumer purchase intention.